2021
DOI: 10.5958/0974-0279.2021.00008.2
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption in India: Probability and demand

Abstract: This study analyses the dietary and fish consumption patterns of Indian households and the determinants of these patterns. A hike in the price reduced demand and the probability of consumption. High-income households consumed more fish than middle-and low-income households, but low-income households spent a high proportion of their total household expenditure on fish. An increase in per capita income raised demand and the probability of consumption. Consumption is driven also by the education, age, and househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A correlation between fish consumption levels and the number of household individuals has been found in some studies. Fish consumption was found to be positively correlated with household size in one study (Marushka et al, 2021), but such a positive correlation was not found in India by Paramasivam and Malaiarasan (2021). Gbigbi (2021) also found a positive relationship between frozen fish consumption and household size.…”
Section: Resultsmentioning
confidence: 95%
“…A correlation between fish consumption levels and the number of household individuals has been found in some studies. Fish consumption was found to be positively correlated with household size in one study (Marushka et al, 2021), but such a positive correlation was not found in India by Paramasivam and Malaiarasan (2021). Gbigbi (2021) also found a positive relationship between frozen fish consumption and household size.…”
Section: Resultsmentioning
confidence: 95%